Examining obstacles that impede the speaking of English in literacy classrooms: a case of two primary schools in the Eastern Cape Province, South Africa - Kleinbooi, Cingile; Moffat, Betina; Linake, Manthekeleng Agnes (Penerbit Universiti Kebangsaan Malaysia, 2024)
Learners often encounter impediments that hamper their ability to proficiently speak English. This study sought to research and determine the obstacles that impede the speaking of English in literacy classrooms. In particular, the study addressed the following research objectives: (i) to identify the language of teaching and learning that is primarily used in English First Additional Language (EFAL) literacy classrooms, and (ii) to examine why rural primary schools lack English speaking practices. Semi-structured interviews were used to collect primary data from two Subject Education Specialists, four Grade 4 EFAL teachers, and two Heads of Department from selected primary schools. Data was analysed using inductive thematic analysis. Interaction theory informed the study, as this theory emphasises the relevance of inputs and modified interaction(s) with respect to learning a second language. Multifaceted challenges impede the speaking of English in literacy classrooms, and these include lack of confidence, limited vocabulary, and limited opportunities to practice speaking. Teachers should minimise using code-switching teaching strategy in Grade 4 EFAL literacy classrooms, as this practice can further delay learners’ understanding of course content and hinder their proficiency in English. Rather, alternative techniques have to be developed and employed to improve speaking of English in the classroom.